2016
DOI: 10.1016/j.jcin.2015.11.045
|View full text |Cite
|
Sign up to set email alerts
|

Transcarotid Transcatheter Aortic Valve Replacement

Abstract: Transcarotid vascular access for TAVR is feasible and is associated with encouraging short- and medium-term clinical outcomes. Prospective studies are required to ascertain if transcarotid TAVR yields equivalent results to other nonfemoral vascular access routes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
43
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 130 publications
(45 citation statements)
references
References 24 publications
1
43
1
Order By: Relevance
“…35,[46][47][48] Previous reports demonstrated the feasibility and safety of the TC approach, mostly with the Medtronic CoreValve THV. 43,49,50 Our experience with the SAPIEN devices is also reassuring.…”
Section: Transcarotid Approachmentioning
confidence: 88%
See 2 more Smart Citations
“…35,[46][47][48] Previous reports demonstrated the feasibility and safety of the TC approach, mostly with the Medtronic CoreValve THV. 43,49,50 Our experience with the SAPIEN devices is also reassuring.…”
Section: Transcarotid Approachmentioning
confidence: 88%
“…The minimally-invasive surgery of the TC pathway has been mastered by numerous heart teams and recently it has been reported to have similar outcomes to TF access in terms of mortality and morbidity. 49 Recent studies reported a mortality of 6.3 % at 30 days and 16.7 % at one year. Furthermore, rates of 30-day cerebrovascular events in our registry were similar to existing data with transfemoral TAVI, 51 in particular the rate of 30-day stroke was under 2.5 % with TC TAVI.…”
Section: Transcarotid Approachmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite a paucity of randomized data on alternate extra-thoracic access such as trans-carotid, subclavian or trans-axillary, single center experience suggests these approaches compare favorably to transthoracic, with acceptable rates of bleeding and vascular access complications (17,22,23). None of these had systematic follow-up imaging or independent adjudication.…”
Section: Discussionmentioning
confidence: 99%
“…Combined, these data suggest that there is likely to be little benefit of TAVR over SAVR in operable patients who are ineligible for transfemoral access because of small or diseased iliofemoral arteries. However, newer options for percutaneous or surgical minimally invasive alternate access, such as transcaval,51 subclavian,52 transaxillary,53 or carotid,54 have been shown to be safe and appear to avoid the morbidity of transthoracic access, although none have been compared with transthoracic access in a randomized trial. Some can be performed with patients under conscious sedation, allowing rapid ambulation after TAVR and shorter hospital length of stay.…”
Section: Do Clinical Trials Of Tavr In Low‐risk Patients Herald the Ementioning
confidence: 99%